The Correlation between Lipid Profile and Smoking (Indian Journal of Forensic Medicine & Toxicology, 2020)
The objectives were to find out the alterations in serum lipid status among adult male smokers and nonsmokers in Maysan Province, south of Iraq, as well as to evaluate the relationship between the heavinessof smoking and dyslipidemia in smoker subjects. A comparative study was achieved on 160 men with aged30-63 years which were grouped to smokers and nonsmokers, among them 120 individuals were smokersand the other 40 were nonsmokers. According to the intensity of smoking, the smoker group is divided againinto three subgroups: mild (A), moderate (B), and heavy (C) smokers. The concentrations of total cholesterol(TC), high density lipoprotein-c (HDL-c), triglycerides (TG), low density lipoprotein-c (LDL-c) and verylow density lipoprotein-c (LDL-c) were measured and calculated. The results revealed that concentrationsof serum lipid profiles in smokers were significantly higher than that of nonsmokers except in case of highdensity lipoprotein-c which was significantly reduced among smokers. In addition to that the lipid profilehad a significant correlation with the cigarette numbers of that smoked daily; the mean values of all lipidfractions except HDL-c were noticeably increased from group A to group C, while they were decreasedin the case of HDL-C. There were significantly different between nonsmokers and different groups of thesmoker, the values of TC of groups A, B, and group C were (178.6, 181.7, and 183.5) mg/dl respectively.According to similar arrangement of above smoker groups, the mean values of TG were (238.4, 245.2,and 248.7) mg/dl. In case of HDL- c, they were (31.5, 28.4, and 26.8) mg/dl. Among LDL-c level, theywere (194.8, 203.8, and 204.9) mg/dl. In VLDL- c level, they were (47.7, 48.2, and 50.5) mg/dl. Thefindings of the study showed that smokers (especially heavy smokers) are at much greater risk of initiatingatherosclerotic plaques and various heart diseases than non-smokers.